Simulation Of C-Check Maintenance Task Card Distribution Using Vogel's Approximation Method - Ian Maccari De Carlini; Mufti Arifin; Ayu Martina (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2025)
Maintenance of an aircraft requires reliable and responsible manpower. Manpower and manhour are needed to perform scheduled and unscheduled maintenance. C-Check maintenance requires a long time for the aircraft to operate again. Therefore, it is necessary to optimize the task card in the maintenance personnel group based on the required task card manhour. Simulation of task card distribution is needed to find the optimum C-Check work group. The method in this study uses Vogel's Approximation Method (VAM) as the main calculation and Northwest Corner (NWC) as the comparison, where VAM and NWC are included in operations research. This study aims to simulate the distribution of C-Check maintenance task cards by adjusting the manhour of the personnel group and the manhour task card required so that the maintenance personnel group can perform the task optimally. The analysis results obtained are manhour requirements in the task card group as demand, the ability of each maintenance personnel group as supply, and the multiplying factor between actual and maintenance program as transportation costs. The results of the calculation of manhour distribution using the Vogel's approximation method (VAM) calculation obtained a total manhours of 724.5 manhours and for the northwest corner (NWC) calculation obtained a total manhours of 902.8 manhours. Thus, the VAM calculation results in cheaper manhour costs compared to the NWC calculation.